S-band planar strip array antennas without dielectric substrate - Martynyuk, S. Y.; Nazarenko, S. B. (Видавництво Національного університету "Львівська політехніка", 2009)
Novel designs of two S-band 4-elemnt (2×2) planar strip array antennas for wireless local area networks (WLAN) exploring the standard IEEE802.11b)g) are presented. The radiating elements of the proposed arrays are metal strip stacked patches, that allow to achieve frequency bandwidth more than 10%. The distinguishing feature of the designs is that strip arrays are air filled and completely free from using any dielectric substrates for holding the radiating patch elements. Manufactured prototypes of the arrays demonstrate good mechanical stability of proposed approach. Measured radiation patterns and frequency characteristic of VSWR are well agreed with theoretical models.
Keywords: microstrip antenna; microstrip antenna array; stacked patch antenna